The Pilgrim's Progress - Bunyan, John; Edited with an Introduction and Notes by N. H. Keeble (Oxford, New York Oxford University Press, 1998)
"The Pilgrim's Progress (Part I 1678/Part II 1684) holds a unique place in the history of English literature. No other seventeenth-century work except the King James Bible, nothing from the pen of a writer of Bunyan's social class in any period, and no other Christian work, has enjoyed such an extensive readership." "The pilgrim Christian, Mr Worldly Wiseman, Giant Despair, Hopeful, and Ignorance are engaged in a powerful drama set against a solidly realistic background of town and country. Bunyan captures the speech of ordinary people as accurately as he depicts their behaviour and appearance and as firmly as he realizes their inner emotional and spiritual life. The tale is related in language remarkable for its beauty and simplicity, and is spiced with Bunyan's acute and satirical perceptions of the vanity and hypocrisy of his own society."--Jacket.
Include Notes, Glossary and Index
Keywords: Christian pilgrims and pilgrimages -- Christian life -- Puritan movements -- Bunyan, John, 1628-1688 -- Salvation